2012
DOI: 10.1177/0009922812443732
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Decision Making About Human Papillomavirus Vaccination Among 11- to 12-Year-Old Girls and Their Mothers

Abstract: Introduction The aims of this qualitative study were to explore (a) the factors influencing mothers’ decisions to vaccinate 11- to 12-year-old daughters against human papillomavirus (HPV) and (b) the mothers’ and daughters’ perspectives about HPV vaccine–related decision making. Methods Participants were girls (N = 33) who had received an HPV vaccine and their mothers (N = 32), recruited from suburban and urban pediatric practices. Semistructured interviews were conducted with girls and mothers separately, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 35 publications
4
82
0
Order By: Relevance
“…4,19,74,78,79 Indeed, some parents indicated a preference for vaccinating in the preteen years specifically because they viewed adolescents as having little say during this 11 Cross-sectional, online survey rout rout F, M 776 National sample of pediatricians and family physicians Gilkey, 2016 60 Cross-sectional, online survey rout rout F, M 1495 National sample of parents of adolescents (ages 11-17) Gilkey, under review 16 Cross-sectional, online survey rout rout F, M 1484 National sample of parents of adolescents (ages [11][12][13][14][15][16][17] (Continued on next page) time. 18,80 In contrast, other studies found that adolescents did play a role in communication and decision-making in clinical settings, one which increased with age, maturity, and social privilege. 18,27,71,73,76,80 For some parents, the desire to maximize adolescents' role was even a reason for delaying HPV vaccination.…”
Section: Communication Rolesmentioning
confidence: 90%
See 3 more Smart Citations
“…4,19,74,78,79 Indeed, some parents indicated a preference for vaccinating in the preteen years specifically because they viewed adolescents as having little say during this 11 Cross-sectional, online survey rout rout F, M 776 National sample of pediatricians and family physicians Gilkey, 2016 60 Cross-sectional, online survey rout rout F, M 1495 National sample of parents of adolescents (ages 11-17) Gilkey, under review 16 Cross-sectional, online survey rout rout F, M 1484 National sample of parents of adolescents (ages [11][12][13][14][15][16][17] (Continued on next page) time. 18,80 In contrast, other studies found that adolescents did play a role in communication and decision-making in clinical settings, one which increased with age, maturity, and social privilege. 18,27,71,73,76,80 For some parents, the desire to maximize adolescents' role was even a reason for delaying HPV vaccination.…”
Section: Communication Rolesmentioning
confidence: 90%
“…18,80 In contrast, other studies found that adolescents did play a role in communication and decision-making in clinical settings, one which increased with age, maturity, and social privilege. 18,27,71,73,76,80 For some parents, the desire to maximize adolescents' role was even a reason for delaying HPV vaccination. 80 Studies suggested that parent-adolescent decisions were largely concordant and that most dyads ultimately reached agreement about the vaccination decision, but they sometimes looked to providers for guidance in the case of initial disagreement.…”
Section: Communication Rolesmentioning
confidence: 90%
See 2 more Smart Citations
“…By giving parents prior notice that their children will be due to receive HPV vaccine, providers may be able to give parents more time to prepare. 9,25 Finally, given the dearth of data on HPV vaccine refusal and delay, additional research is needed to explore topics such as why parents who initially refuse or delay HPV vaccine later go on to get the vaccine. Understanding how parental refusal and delay interact with other key determinants of under-immunization (e.g., absent or low-quality provider recommendations) is also important.…”
Section: Discussionmentioning
confidence: 99%